2019
DOI: 10.1007/978-3-030-32245-8_21
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Esophageal Gross Tumor Volume Segmentation in PET/CT Using Two-Stream Chained 3D Deep Network Fusion

Abstract: Gross tumor volume (GTV) segmentation is a critical step in esophageal cancer radiotherapy treatment planning. Inconsistencies across oncologists and prohibitive labor costs motivate automated approaches for this task. However, leading approaches are only applied to radiotherapy computed tomography (RTCT) images taken prior to treatment. This limits the performance as RTCT suffers from low contrast between the esophagus, tumor, and surrounding tissues. In this paper, we aim to exploit both RTCT and positron em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 18 publications
0
45
0
Order By: Relevance
“…The use of CNN (1,2) in radiotherapy has been shown to be a state-of-the-art method for organs and tumor segmentation in several disease sites (3)(4)(5)(6)(7)(8)(9)(10)(11). Various notable developments in the use of deep learning methods for organ segmentation have improved the precision of automatic segmentation (12)(13)(14)(15). However, considerable variability in medical images can cause unpredictable errors, even with the use of the best model.…”
Section: Introductionmentioning
confidence: 99%
“…The use of CNN (1,2) in radiotherapy has been shown to be a state-of-the-art method for organs and tumor segmentation in several disease sites (3)(4)(5)(6)(7)(8)(9)(10)(11). Various notable developments in the use of deep learning methods for organ segmentation have improved the precision of automatic segmentation (12)(13)(14)(15). However, considerable variability in medical images can cause unpredictable errors, even with the use of the best model.…”
Section: Introductionmentioning
confidence: 99%
“…Although the datasets are not comparable, in [28] an average DSC score of 0.76 ± 0.13 was obtained on scans of 110 patients, using 5-fold cross validation. In [23] a DSC score of 0.75 ± 0.04 for four patients as the test set has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…That work in an expensive pre-processing step encodes spatial context by computing the signed distance transform maps (SDMs) of the GTV, lymph nodes (LNs) and organs at risks (OARs) and then feeds the results with the CT image into a 3D CNN. In another work Jin et al [28] proposed a two-stream chained 3D CNN fusion pipeline to segment esophageal GTVs using both CT and PET+CT scans. They evaluated their approach by conducting a 5-fold cross validation on scans of 110 patients.…”
Section: Related Workmentioning
confidence: 99%
“…Jin et al (10) integrate the RTCT and PET modalities together into a two-stream chained deep fusion framework, which represents a complete workflow for the target delineation in esophageal cancer radiotherapy and pushes forward the state of automated esophageal GTV and CTV segmentation towards a clinically applicable solution. Using extensive five-fold cross-validation on 110 esophageal cancer patients, they also demonstrate that both the proposed two-stream chained segmentation pipeline that effectively fuses the CT and PET modalities via early and late 3D deep-network-based fusion and the PSNN model can significantly improve the accurate GTV segmentation over the previous state-of-the-art work (11). Yousefi S. et al (12) found that the proposed method, dubbed dilated dense attention Unet (DDAUnet), could segment the gross tumor volume with a mean surface distance of 5.4 ± 20.2mm, demonstrating that a simplified clinical workflow based on CT alone could allow to automatically de-lineate the esophageal GTV with acceptable quality.…”
Section: Introductionmentioning
confidence: 87%